2011
DOI: 10.1002/path.2980
|View full text |Cite
|
Sign up to set email alerts
|

Mouse intermittent hypoxia mimicking apnoea of prematurity: effects on myelinogenesis and axonal maturation

Abstract: Premature babies are at high risk for both infantile apnea and long-term neurobehavioral deficits. Recent studies suggest that diffuse structural changes in brain white matter are a positive predictor of poor cognitive outcomes. Since oligodendrocyte maturation, myelination, axon development and synapse formation mainly occur in the 3rd trimester of gestation and 1st postnatal year, infantile apnea could lead to and/or exaggerate white matter impairments in preterm neonates. Therefore, we investigated oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 81 publications
6
44
1
Order By: Relevance
“…To test this hypothesis we developed a mouse model where WMI was induced by non-lethal IH stress and the phenotype was characterized by cerebral hypomyelination associated with permanent neurofunctional deficit, without cell degeneration in the brain. In contrast to reported models of WMI induced by IH mimicking severe hypoxemic event associated with apnea of prematurity (Cai et al, 2012;Oorschot et al, 2013), our paradigm of IH simulates only mild, non-bradycardia-associated, repetitive hypoxemic episodes, the IH-pattern of unknown neurological significance, yet the most commonly seen in human premature infants.…”
Section: Introductionmentioning
confidence: 75%
“…To test this hypothesis we developed a mouse model where WMI was induced by non-lethal IH stress and the phenotype was characterized by cerebral hypomyelination associated with permanent neurofunctional deficit, without cell degeneration in the brain. In contrast to reported models of WMI induced by IH mimicking severe hypoxemic event associated with apnea of prematurity (Cai et al, 2012;Oorschot et al, 2013), our paradigm of IH simulates only mild, non-bradycardia-associated, repetitive hypoxemic episodes, the IH-pattern of unknown neurological significance, yet the most commonly seen in human premature infants.…”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, this is the first study to evaluate the blood-brain permeability in a murine model of sleep apnea. Cai et al (2012) reported hypomyelination in a mice model of infantile sleep apnea. They found a reduction in proportion of myelinated fibers in the external capsule, striatum, fornix, and cerebellum.…”
Section: Discussionmentioning
confidence: 96%
“…[125][126][127] The epidemiological and cohort studies linking sleep apnea to kidney disease led Sun and colleagues to examine the effects of sleep apnea on renal function and morphology in a mouse model of intermittent hypoxia. 127 Animals were randomly assigned to either intermittent hypoxia or control groups and primary measures were collected after 3 days, and later at 1, 2, and 8 weeks.…”
Section: Animal Model Of Sleep Apnea-induced Renal Damagementioning
confidence: 99%